PENGARUH KINERJA KEUANGAN TERHADAP PRICE TO BOOK VALUE (PBV) PADA PERUSAHAAN RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2010-2014 - B31111072, MARIA YESSY CHRISTY (Jurnal Manajemen Update, 2016)
A high number of the increasing value of the company is a long-term goal that should be achieved by the company that will be reflected in the market price of the shares as investors' assessment of the company can be observed through  the  movement  of  the  company's  stock  price  traded  on  the  stock exchange for companies that have gone public. This research aimed to analyze financial performance that affect the value of the company at a retail company listed on Indonesian Stock Exchange (IDX) in 2010-2014.   Population in this research were 23 companies listed on the Indonesian Stock Exchange (IDX). Samples collected as many as 16 retail companies selected by porposive  sampling.  Independent  variables in  this  research  are Liquidity (Current Ratio), Leverage (Debt to Equity Ratio), Activity (Total Asset Turnover), and Profitability (Return On Assets), while the dependent variable is the Value of the Company (Price to Book Value). The method that used for the analysis in this research is multiple regression analysis.   The results showed that Liquidity has negative and insignificant effect on the Value of the Company, while Leverage has positive and insignificant effect on Company’s Value, as well as Activity has positive and insignificant effect on the Value of the Company, and Profitability has positive and significant impact on the Company's Value. Coefficient of determination is 30.5%. That result indicates  the  magnitude  of  the  ability  of  independent  variables  explain dependent variable, while the 69,5% explained by the other variables.       Key Word: Liquidity, Leverage, Activity, Profitability, and Price to Book Value